Kunxian capsule alleviates podocyte injury and proteinuria by inactivating β-catenin in db/db mice - Jin, Bo; Liu, Jing; Zhu, Yan; Lu, Jian; Zhang, Qingyan; Liang, Yan; Shao, Qiuyuan; Jiang, Chunming (Frontiers in Medicine, 2023)
Background: Diabetic kidney disease (DKD) remains the primary cause of end-stage renal disease (ESRD) globally, but treatment options are limited. Kunxian capsule (KXC) has being utilized for the treatment of autoimmune diseases and IgA nephropathy in China. However, its effect on DKD remains poorly investigated. Therefore, this study aimed to explore the protective effect of KXC in db/db mice and elucidate its underlying mechanism. Methods: The renoprotective effects of KXC were accessed in a DKD mouse model using male BKS db/db diabetic mice. After 8 weeks of treatment, urinary albumin-to-creatinine ratio (UACR), blood biochemical parameters, renal histopathological manifestation, as well as podocyte ultrastructural changes were evaluated. Additionally, the expression of podocyte epithelial-to-mesenchymal transition (EMT) marks (WT1, Zo-1, and Collogen I (Col1a1)) were quantitatively analyzed. Furthermore, we explored the role of KXC on the β-catenin signaling pathway to elucidate the underlying mechanism of KXC’s renoprotective effect. Results: KXC treatment effectively reduced albuminuria and attenuated renal structural abnormalities in db/db mice. Additionally, KXC restored the protein and mRNA expression of WT1 and ZO-1, while suppressing the expression of Col1a1 in db/db mice, indicating its ability to alleviate podocyte EMT. Mechanistically, KXC exerted a significant suppressing effect on the activation of β-catenin signaling in diabetic kidneys. Conclusion: KXC has the potential to protect podocytes during DKD by alleviating podocyte EMT through inactivating β-catenin signaling.